Hidróxido de sódio na neutralização do ácido sulfúrico no deslintamento de sementes de algodão - Piva, Diana Lourdes Pizzi Dal (2013)
This paper aims to evaluate the physiological performance of cotton seeds that where chemically delinted with sulfuric acid and neutralized with sodium hydroxide. It was used cotton seeds (Gossypium hirsutum L.), of the FIBRAMAX 966 variety, produced in the Midwest region of Brazil, in the city of Primavera do Leste Mato Grosso. During the treatment and storage phases, the seeds remained in the Itaquere seeds delinting plant (UDESIL), which is located in the Industrial Park of Primavera do Leste, and the sowing was held in the experimental area of the agronomy course of the College of Agricultural and Accurate Sciences - UNIC Primavera do Leste Unit. The treatments consisted of sodium hydroxide concentrations (0%,, 10%, 20% and 30%) and the experimental delimitation used was entirely randomized, with five repetitions. The seed physiological quality was evaluated before storage and after ten months of storage, by PH evaluation, one thousand seeds weight, water content, germination, first counts of germination, germination speed rate, field emergency, first count of emergency and emergency speed rate. The seeding emergence, after ten months of storage, showed an increasing trend with the elevations of NaOH concentrations. The chemical delinting with sodium hydroxide, as its concentration, affects the performance of the cotton seeds, during storage.